2019
DOI: 10.4028/www.scientific.net/msf.944.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Surface Treatments on Fatigue Life of 7050 Al Alloy

Abstract: The fatigue life of 7050 Al alloy samples after different surface treatments, i.e., as-machined, anodizing, shot peening, and shot peening followed by anodizing, had been tested. The shot peening treatment specimens presented the longest average fatigue life. The fatigue life of anodizing treatment specimens decreased by 69.3% and 78.8% at 215 MPa and 260 MPa stress levels than as-machined ones. Introducing the shot peening treatment before anodizing can increase the fatigue life by 220% / 296.9% at 215 MPa/26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
2
Order By: Relevance
“…It is commonly reported that the anodizing process induces surface tensile stress states, as highlighted in several past scientific papers. [44][45][46] However, the analysis of the reported data shows a trend contrary to expectations, in which the anodizing process in tartaric-sulfuric solution appears to induce slight compression, in both the axial and transverse directions. It should be pointed out, however, that the extremely small thickness of the anodic layer causes residual stress measurements by X-ray diffractometry (penetration depth of about 10 μm) to be made on a volume of material that does not consist entirely of the anodic layer but rather largely of base material.…”
Section: Residual Stress Analysiscontrasting
confidence: 67%
See 1 more Smart Citation
“…It is commonly reported that the anodizing process induces surface tensile stress states, as highlighted in several past scientific papers. [44][45][46] However, the analysis of the reported data shows a trend contrary to expectations, in which the anodizing process in tartaric-sulfuric solution appears to induce slight compression, in both the axial and transverse directions. It should be pointed out, however, that the extremely small thickness of the anodic layer causes residual stress measurements by X-ray diffractometry (penetration depth of about 10 μm) to be made on a volume of material that does not consist entirely of the anodic layer but rather largely of base material.…”
Section: Residual Stress Analysiscontrasting
confidence: 67%
“…The untreated specimens exhibit a slight compressive tensional state (about −100 MPa) along both in axial and transverse directions. It is commonly reported that the anodizing process induces surface tensile stress states, as highlighted in several past scientific papers 44–46 . However, the analysis of the reported data shows a trend contrary to expectations, in which the anodizing process in tartaric–sulfuric solution appears to induce slight compression, in both the axial and transverse directions.…”
Section: Resultsmentioning
confidence: 75%
“…A general compressive stress state is observed over the entire surface, both in the longitudinal and transverse directions. Generally, the anodizing process is associated with the development of tensile residual stresses at the surface of the component 21,22 ; however, in a previous study 23 conducted on the same aluminum alloy but employing a different electrolyte, the development of a slight compressive stress state following anodizing was observed, as shown in the present work.…”
Section: Surface Quality and Thickness Of Tsa-anodic Filmcontrasting
confidence: 56%
“…In particular, their attention focused on the beneficial improvements determined by the application of shot peening surface treatment before the anodizing process to induce the presence of a compressive layer of residual stress beneath the surface of the component. Li et al 23 came to the same conclusion by analyzing the fatigue behavior of AA7050 T7451 specimens that were shotpeened before the SAA process.…”
Section: Introductionmentioning
confidence: 69%
“…21 Besides, the anodic film cannot be too thick because thick anodic film may compromise fatigue performance of the anodized aluminum alloy components. 32 Another strategy is to introduce complex ions into the pores of the anodic film, which allows complexing reaction between the complex ions and cations trapped in the film material, providing additional sealing to the anodic film. This is one of the theoretical basis for designing new anodizing processes such as TSA 6,33,34 and boric-sulfuric acid anodizing (BSA).…”
Section: Discussionmentioning
confidence: 99%